PENDEKATAN AGRIBISNIS DALAM PENGEMBANGAN PERTANIAN LAHAN KERING *) (Kasus Lahan Kering di Kabupaten Buleleng, Bali) - MADE ANTARA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2004)
Agribusiness has been a new discourse in development of agriculture andeconomics in Indonesia. Implementation of agribusiness concept promise many kindof positive benefit for development of agriculture and economics, so that everyagricultural activity and which related to agriculture always use agribusinessapproach.Development of dry land in East Bali generally and in Buleleng Regencyspecially with grant support of European economic community (MEE) also use ofagribusiness approach, expected can improve prosperity of the farmers in dry land.Therefore, the target of writing of this paper is to present stages and informationapproach of agribusiness in development of dry land.From result study and reasoning empirical, so can be told that development ofdry land agriculture in east Bali generally and in Buleleng regency specially troughagribusiness approach is a precise and correct steps, because this approach tointegrate vertically from upstream activity to downstream and by horizontal amongvarious sectors, so that will be able to create feasible profit for farmers in dry landfarming.In effort to realize development of dry land agriculture through agribusinessapproach which has potency to increase of farmer’s income and also to eliminateeconomics gap, need support of political will of government (center, province, andregency) and all of society include Non Governmental Organization (NGO) inBuleleng regency. They can be important actors in its realizing, either throughdevelopment strategy socialization or also through accompanying of farmer indevelopment of advantage agribusiness and co-operation of agribusiness.In the end of project require to evaluate by independent institution aboutproject impact of European Economic Community grant toward improving of socioeconomiccondition of the farmer as target of project with analysis methods of beforeand after project or with and without project.